Targeted mutation analysis of endometrial clear cell carcinoma. Issue 5 (13th January 2015) - Hoang, Lien N; McConechy, Melissa K; Meng, Bo; McIntyre, John B; Ewanowich, Carol; Gilks, Cyril Blake; Huntsman, David G; Köbel, Martin; Lee, Cheng‐Han
<x xml:space="preserve">Abstract</x> Aims Endometrial clear cell carcinomas (CCC) constitute fewer than 5% of all carcinomas of the endometrium. Currently, little is known regarding the genetic basis of endometrial CCC. Methods and results We performed genomic and immunohistochemical analyses on 14 rigorously reviewed pure endometrial CCC. The genomic analysis consisted of sequencing the coding regions of 26 genes implicated previously in endometrial carcinoma. Twelve of 14 tumours displayed a prototypical CCC immunophenotype [napsin A+, hepatocyte nuclear factor‐1β (HNF1β+) and oestrogen receptor−] and all showed intact mismatch repair protein expression. We detected mutations in 11 of 14 tumours, and there was a predominance of mutations involving genes that are mutated more frequently in endometrial serous carcinomas than in endometrioid carcinomas. Two tumours displayed a prototypical serous carcinoma mutation profile (concurrent TP53 and PPP2R1A mutations, without PTEN, CTNNB1 or ARID1A mutation). No mutations in PTEN, CTNNB1 or POLE were identified. Conclusions The overall mutation profile of this cohort of endometrial CCC appears to be more serous‐like than endometrioid‐like, with a minor subset in the TP53‐mutated CCC showing serous carcinoma profile. These findings provide new insights into the molecular features of morphologically prototypical endometrial CCC, and underscore the need for further investigations into the oncogenesis of endometrial CCC.